Effects of Direct- and Indirect-Acting Serotonin Receptor Agonists on the Antinociceptive and Discriminative Stimulus Effects of Morphine in Rhesus Monkeys - Li, Jun-Xu (Nature Publishing Group, 2011)
Serotonergic (5-HT) systems modulate pain, and drugs acting on 5-HT systems are used with opioids to treat pain. This study examined the effects of 5-HT receptor agonists on the antinociceptive and discriminative stimulus effects of morphine in monkeys. Morphine increased tail-withdrawal latency in a dose-related manner; 5-HT receptor agonists alone increased tail-withdrawal latency at 50 °C but not 55 °C water. The antinociceptive effects of morphine occurred with smaller doses when monkeys received an indirect-acting (fenfluramine) or direct acting (8-OH-DPAT, F13714, buspirone, quipazine, DOM, and 2C-T-7) agonist. The role of 5-HT receptor subtypes in these interactions was confirmed with selective 5-HT(1A) (WAY100635) and 5-HT(2A) (MDL100907) receptor antagonists. None of the 5-HT drugs had morphine-like discriminative stimulus effects; however, fenfluramine and 5-HT(2A) receptor agonists attenuated the discriminative stimulus effects of morphine and this attenuation was prevented by MDL100907. The 5-HT(1A) receptor agonists did not alter the discriminative stimulus effects of morphine. Thus, 5-HT receptor agonists increase the potency of morphine in an assay of antinociception, even under conditions where 5-HT agonists are themselves without effect (ie, 55 °C water), without increasing (and in some cases decreasing) the potency of morphine in a drug discrimination assay. Whereas 5-HT(2A) receptor agonists increase the potency of morphine for antinociception at doses that have no effect on the rate of operant responding, 5-HT(1A) receptor agonists increase the potency of morphine only at doses that eliminate operant responding. These data suggest that drugs acting selectively on 5-HT receptor subtypes could help to improve the use of opioids for treating pain.